2018
DOI: 10.1021/acschemneuro.8b00545
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanoparticles Containing Mechanism Based Peptide Inhibitors Reduce Polyglutamine Aggregation in Cell Models and Alleviate Motor Symptoms in a Drosophila Model of Huntington’s Disease

Abstract: Detailed study of the molecular mechanism behind the pathogenesis of Huntington’s disease (HD) suggests that polyglutamine aggregation is one of the fundamental reasons for HD. Despite the discovery of many potential molecules, HD therapy is still limited to symptomatic relief. Among these molecules, few mechanism based peptide inhibitors of polyglutamine aggregation (QBP1, NT17 and PGQ9P2) have shown promising activity; however, poor blood-brain barrier (BBB) penetration, low bioavailability, and low half-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The therapeutic potential of many molecules remains unexplored, because of their intrinsic properties (poor water solubility, poor pharmacokinetic properties), and difficulty to penetrate the blood-brain barrier. There is thus a growing necessity of developing drug delivery system, such as nanoparticules, to improve target specificity and increase bioavailability of a drug in the brain [171,172].…”
Section: Preventing Matxn7 Accumulationmentioning
confidence: 99%
“…The therapeutic potential of many molecules remains unexplored, because of their intrinsic properties (poor water solubility, poor pharmacokinetic properties), and difficulty to penetrate the blood-brain barrier. There is thus a growing necessity of developing drug delivery system, such as nanoparticules, to improve target specificity and increase bioavailability of a drug in the brain [171,172].…”
Section: Preventing Matxn7 Accumulationmentioning
confidence: 99%
“…Published in 2019, Joshi et al, designed peptide-loaded PLGA NPs coated with polysorbate 80 to act on mHtt aggregation. QBP1, NT17, and PGQ 9 P 2 are oligonucleotides exhibiting great inhibitory potential against mutant huntingtin protein aggregation [ 73 , 74 ]. In this study, nanoprecipitation peptide-loaded PLGA NPs were prepared to obtain NPs from 158 to 180 nm in diameter with a low PdI (<0.100) and a ζ potential between −23.3 and −27.5 mV.…”
Section: Plga Nps For Neuroprotective Drug Delivery In Neurological Disorder Therapymentioning
confidence: 99%
“…: 50.5 to 73.0% In vitro: PC12 cells In vivo: healthy CD57/BL6 mice (with MPTP group) Improve locomotor activity over time Improve brain delivery by intranasal route Enhance dopamine concentration in the brain compared to the blood [ 99 ] Rasagiline Double emulsion/solvent evaporation ø: 221.7 ± 5.7 nm PdI: 0.388 ± 0.860 ζ potential: −36.1 ± 4.4 mV E.E. : 29.2 ± 1.8% In vivo: healthy and Parkinson Wistar rats Inhibit MAO-B enzyme Prevent neuronal damage caused by oxidative stress [ 67 ] Huntington’s Disease Peptides QBP1, NT17, and PGQ 9 P 2 Nanoprecipitation ø: 158 to 180 nm PdI: 0.031 to 0.066 ζ potential: −23.3 to −27.5 mV In vitro: MDCK, Neuro 2A and PC12 cell model of HD In vivo: healthy mice, Drosophila, larvae, and adult fly model of HD Inhibit mHtt aggregation Restore motor activity [ 74 ] Cholesterol Nanoprecipitation ø: 200 to 300 nm PdI: 0.090 to 0.300 ζ potential: −8 to −12 mV D.L. : 0.7 to 2.5% E.E.…”
Section: Plga Nps For Neuroprotective Drug Delivery In Neurological Disorder Therapymentioning
confidence: 99%
“…It has also been shown that the loading of thymoquinone into the SL NPs markedly suppresses the progression of HD by increasing the activity of ATPase enzymes and reducing the production of inflammatory markers and the nuclear translocation of phosphorylated nuclear factor κB in rat model (Ramachandran and Thangarajan, 2018). Moreover, the encapsulation of peptide-based polyglutamate aggregation inhibitors into PLGA NPs can enhance their protective effects in Neuro 2A and PC12 cellular models as well as its biocompatibility in Drosophila model of HD (Joshi et al, 2019). In both neuronal cell and mouse model, poly(trehalose) NPs have also been reported to be extremely efficient in inhibiting the progression HD by suppressing the accumulation of mutant huntingtin protein (Debnath et al, 2017).…”
Section: Huntington Disease (Hd)mentioning
confidence: 99%